Gender and Resistance in the Works of Jhumpa Lahiri and Meena Kandasamy: A Study of Identity and Rebellion - Renu (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This paper explores the theme of gender and resistance in contemporary Indian literature, focusing on the works of Jhumpa Lahiri and Meena Kandasamy. While Lahiri’s short stories and novels predominantly examine the quiet rebellion of women against patriarchal structures within the Indian diaspora, Kandasamy’s poetry and prose evoke a much more explicit resistance against caste oppression and gender-based violence within Indian society. By analyzingLahiri’sThe Lowland and Kandasamy’s When I Hit You: Or, A Portrait of the Writer as a Young Wife, this paper investigates how both authors interrogate societal expectations, subvert traditional gender roles, and carve spaces for female autonomy and agency. Using feminist literary criticism and postcolonial frameworks, this paper contends that Lahiri and Kandasamy offer nuanced portrayals of the complex intersections of gender, identity, and resistance in contemporary Indian literature.